Advancements in Biomonitoring and Remediation Treatments of Pollutants in Aquatic Environments - Ferri, Elida Nora (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of a group of peer-reviewed scientific papers dealing with both the evaluation and the solution of the complex but pressing problem of water source pollution. In the case of both fresh and marine water, the environmental and health protection aspects are closely linked. Monitoring activities supply continuous information on the contamination levels in inland surface, ground, and coastal waters, providing an alert in case of increased or new contamination and monitoring the effectiveness of remediation strategies. On the other hand, new or improved remediation and bioremediation tools are urgently needed to tackle the scarcity of safe drinking water. The papers in this book represent interesting starting points for future researches.